2022
DOI: 10.1155/2022/7277562
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Cardioprotective Effects of Curcumin against Doxorubicin-Induced Cardiotoxicity: A Systematic Review

Abstract: Objective. This study aimed to review the potential chemoprotective effects of curcumin against the doxorubicin-induced cardiotoxicity. Methods. According to the PRISMA guideline, a comprehensive systematic search was performed in different electronic databases (Web of Science, PubMed, and Scopus) up to July 2021. One hundred and sixty-four studies were screened in accordance with a predefined set of inclusion and exclusion criteria. Eighteen eligible articles were finally included in the current systematic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 127 publications
(235 reference statements)
0
13
0
Order By: Relevance
“…The inflammatory process is a biological phenomenon which occurs in response to tissue damage induced from several harmful stimuli such as chemotherapy, radiation, microbial pathogen infection, and/or wounding [ 116 121 ]. Among the characteristics of inflammation are: elevation in leukocyte migration to injured area, upregulation of pro-inflammatory cytokines, and leukocyte chemotaxis [ 122 , 123 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory process is a biological phenomenon which occurs in response to tissue damage induced from several harmful stimuli such as chemotherapy, radiation, microbial pathogen infection, and/or wounding [ 116 121 ]. Among the characteristics of inflammation are: elevation in leukocyte migration to injured area, upregulation of pro-inflammatory cytokines, and leukocyte chemotaxis [ 122 , 123 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in cells cultured with 20% mouse serum, an increase in cell proliferation of approximately 50% within 24 h was seen in both 4T1 cells and other breast cancer cell lines (data not shown). The trace amounts of curcumin present in serum may have induced the increase in cell proliferation, given the radio-and chemo-protective capacity of curcumin, and it may have promoted the expression of proliferation-inducing molecules (37,38). Gardane et al reported that low concentrations of curcumin (10 μg/ml and 20 μg/ml) stimulated the proliferation of KG-1a cells, whereas high concentrations (30 μg/ml to 100 μg/ml) induced an inhibitory effect (39).…”
Section: Discussionmentioning
confidence: 99%
“…Two recent systematic reviews collected data from in vitro and in vivo studies with curcumin (CC) co-administered as a cardioprotective agent [ 155 , 156 ]. Curcumin is a phytochemical that is obtained from the rhizomes of Curcuma longa L. and it acts as an antioxidant with anti-apoptotic and anti-inflammatory effects on healthy cells.…”
Section: The Critical Role Of Nrf-2-keap I In the Interplay Between C...mentioning
confidence: 99%